2010
DOI: 10.1093/rheumatology/keq246
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro model to investigate joint ochronosis in alkaptonuria

Abstract: We have developed an in vitro model of ochronosis that should contribute to understanding joint destruction in AKU and to the aetiology of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 14 publications
2
63
0
Order By: Relevance
“…Oxidative stress is at the center of AKU pathophysiological scene and ROS injury is crucial in many degenerative diseases (Bocci and Valacchi, 2013; Signorini et al, 2014); oxidative stress is also related to HGA‐induced AKU chondrocyte apoptosis and cartilage degeneration, as we recently reported (Braconi et al, 2010a,b; Tinti et al, 2010, 2011a,2011b; Braconi et al, 2012; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013). There is growing evidence (Armstrong, 2002; Poli et al, 2008) that HNE, generated during the LPO process and here reported to be present in AKU chondroptotic cartilage (Fig.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Oxidative stress is at the center of AKU pathophysiological scene and ROS injury is crucial in many degenerative diseases (Bocci and Valacchi, 2013; Signorini et al, 2014); oxidative stress is also related to HGA‐induced AKU chondrocyte apoptosis and cartilage degeneration, as we recently reported (Braconi et al, 2010a,b; Tinti et al, 2010, 2011a,2011b; Braconi et al, 2012; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013). There is growing evidence (Armstrong, 2002; Poli et al, 2008) that HNE, generated during the LPO process and here reported to be present in AKU chondroptotic cartilage (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Our previous work (Braconi et al, 2010,b; Tinti et al, 2010; Tinti et al, 2011a,2011b; Braconi et al, 2012; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013) suggested that morphological changes of chondrocytes in AKU cartilage may be attributed to apoptosis, but until now no in depth study exists to elucidate if chondroptosis may occur in AKU. Moreover, ultra‐structural observations were complemented with biochemical and proteomic characterization of chondrocytes isolated from the ochronotic cartilage of AKU patients, indicating that AKU chondrocytes are characterized by HGA‐induced apoptosis, protein aggregation, nitric oxide release, and oxidative stress (Tinti et al, 2011a; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent years the defective gene has been mapped and cloned (Pollak et al 1993;Zatkova 2011). An in vitro model and a mouse model are also available to aid in understanding the progression of the disease and screening of therapeutic agents (Preston et al 2014;Taylor et al 2012;Tinti et al 2011). Although advances have been made in understanding AKU there is one area that is still somewhat lacking: the analysis and understanding of what occurs to HGA and the chemical changes that occur as it polymerises that may enable or determine how the pigment interacts with the cells and extracellular matrices of AKU patients' tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The histological reaction of HGA and its polymeric derivative with Schmorl's reagent show identical staining properties to tyrosine and melanin (Tinti et al 2011). The conversion of L-tyrosine to its L-3,4-dihydroxyphenylalanine (L-DOPA) intermediary and melanin is catalysed by tyrosinase and it has been proposed that this could also be involved in the conversion of HGA to its quinone intermediary and subsequent ochronotic pigment (Taylor et al 2016a, b).…”
Section: Introductionmentioning
confidence: 99%